Strategies to tackle non-communicable diseases in Afghanistan: A scoping review - Neyazi, Narges; Mosadeghrad, Ali Mohammad; Afshari, Mahnaz; Isfahani, Parvaneh; Safi, Najibullah (Frontiers in Public Health, 2023)
Non-communicable diseases (NCDs) and their risk factors are the leading cause of death worldwide and contribute to 74.3% of deaths globally in 2019. The burden of NCDs is escalating in Afghanistan. Currently, every seconds, people in Afghanistan are dying of NCDs. Addressing this challenge in Afghanistan needs effective and practical interventions. This study aimed to identify the strategies developed and implemented in countries with low non-communicable premature death. To conduct a scoping review, we followed the six-step Arksey and O'Malley protocol and searched for eligible articles on eight international databases and the gray literature. The study followed the Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) guidelines. The inclusion criteria were English documents and evidence produced up to 30 November 2021 for the control of NCDs. We excluded incomplete texts, duplicates, and dissertations due to lack of access. We used EndNote X9 and MaxQDA software for data management and analysis. We conducted content analysis for this study. A total of 122 documents developed between 1984 and 2021 met the inclusion criteria. We identified 35 strategies from which the most used strategies were related to unhealthy diets and smoking cessation programs. Canada (26.4%), Korea (19.8%), and the United Kingdom (19%) have the most publications on the control and prevention of NCDs among the countries included in the study. Most strategies were implemented over 2 years (41%). This study recommends specific interventions to control and prevent NCDs for the main risk factors of tobacco use, unhealthy diet, physical inactivity, and the main non-communicable diseases such as heart diseases, cancers, diabetes, and chronic obstructive pulmonary diseases. Afghanistan Ministry of Public Health, the WHO country office, and other involved stakeholders can use the findings of this review to design and implement strategies for controlling and preventing NCDs in Afghanistan. International organizations such as the World Health Organization, United Nations Agencies, the World Bank, and other involving communities should invest in strengthening good health governance in Afghanistan. The Afghan Government should focus on promoting and funding health literacy among the public and self-care to control and prevent NCDs.